Regional Convergence between Western and Eastern Indonesia - Vanessa Aurelia; Lucky Permana; Albert Hasudungan; Alvin Desfiandi (Jurnal Ekonomi Pembangunan, 2021)
This article aims to investigate the existence and determinants of regional convergence of western and eastern Indonesia. Regional convergence itself is a condition where eventually, all regions will grow into one similar level of income. Previous studies seem to verify the existence of regional convergence. Based on previous regional economic scholarship. the regional convergence is signified with the significant relationship of past lag real GDP per capita with current GDP per capita.  However, the increasing gap between western and eastern Indonesia in terms of GDP per capita brings into the critical issue of the possible attainment of the existence of regional convergence in Indonesia. In this paper, the fixed effect panel data regression method was utilized to determine the current state of Indonesia’s regional convergence process and to figure out the relationship of education, mining, and financial development to regional economic growth. From the study, regional convergence is found to be insignificant from 2010 to 2019. This study also managed to determine that financial development, mining contribution, the elementary, and high school enrollment rate is positively correlated with economic growth.